Rational Design of Low-Band Gap Star-Shaped Molecules With 2,4,6-Triphenyl-1,3,5-triazine as Core and Diketopyrrolopyrrole Derivatives as Arms for Organic Solar Cells Applications - Zhang, Xinhao; Jin, Ruifa (Frontiers in Chemistry, 2019)
A series of D–A novel star-shaped molecules with 2,4,6-triphenyl-1,3,5-triazine (TPTA) as core, diketopyrrolo[3,4-c]pyrrole (DPP) derivatives as arms, and triphenylamine (TPA) derivatives as end groups have been systematically investigated for organic solar cells (OSCs) applications. The electronic, optical, and charge transport properties were studied using density functional theory (DFT) and time-dependent DFT (TD-DFT) approaches. The parameters such as energetic driving force ΔEL-L, adiabatic ionization potential AIP, and adiabatic electron affinity AEA were also calculated at the same level. The calculated results show that the introduction of different groups to the side of DPP backbones in the star-shaped molecules can tune the frontier molecular orbitals (FMOs) energy of the designed molecules. The designed molecules can provide match well with those of typical acceptors PCBM ([6,6]-phenyl-C61-butyric acid methyl ester) and PC71BM ([6,6]-phenyl-C71-butyric acid methyl ester). Additionally, the absorption wavelengths of the designed molecules show bathochromic shifts compared with that of the original molecule, respectively. The introduction of different groups can extend the absorption spectrum towards longer wavelengths, which is beneficial to harvest more sunlight. The calculated reorganization energies suggest that the designed molecules are expected to be the promising candidates for ambipolar charge transport materials except molecule with benzo[c]isothiazole group can be used as hole and electron transport material. Moreover, the different substituent groups do not significantly affect the stability of the designed molecules.